HUBUNGAN ANTARA SIKAP KERJA DENGAN KELUHAN LOW BACK PAIN PADA PENGRAJIN GAMELAN DI DESA TIHINGAN - Purnama, Pande Made Dwi Ayu; Nurhesti, Putu Oka Yuli; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing, 2023)
Low back pain is a part of musculoskeletal disorders that often occur during work activities. Low back pain complaints are experienced among public and mostly occur among workers such as gamelan craftsman. The process of making gamelan through several stages causes pain that is felt in the body. One factor that influences the onset of pain is work attitude. Non-Ergonomic work attitude will increase the risk of low back pain among workers. This study aimed to determine the correlation between work attitude and low back pain complaints among gamelan craftsmen. This study was a correlative descriptive study. Total sampling was used to recruit 57 respondents. Work attitudes and low back pain complaints are measured using Nordic Body Map (NBM) and REBA questionnaires. Data analysis that used was the Spearman rank test. The result shows that there is a significant and strong correlation with positive direction between work attitudes and low back pain complaints among gamelan craftsmen with p-value < 0,0001, r = 0,653. The result also show that determinant coefficient is 42,6%, it means work attitude has a correlation with low back pain complaints among gamelan craftsmen by 42,6%, Thus, the gamelan craftworkers require to adjust with body position and control the work duration to escape from health risk, such as low back pain.